Psychosocial factors and gender influencing the level of Islamic financial literacy - Siti Hafizah, Abdul Rahim (2014)
The purpose of this study is to assess the level of Islamic financial literacy among the undergraduate students of Islamic finance and banking in Universiti Utara Malaysia. It aims to examine the influence of psychosocial factors which are hopelessness, religiosity and financial satisfaction as well as gender towards Islamic financial literacy. Hypothesized relationships are tested using survey response from a sample of 200 respondents. The result of this study shows that the level of Islamic financial literacy of the respondents is high. A significant difference in Islamic financial literacy is found between the respondents according to the gender and the respondents‟ year of study. Specifically, male have a higher level of Islamic financial literacy compared to female. Meanwhile, the third year‟s students have a higher level of Islamic financial literacy compared to first year and second year students. Additionally, the result indicates that there is a significant relationship between psychosocial factors and Islamic financial literacy. Moreover, it is found that the religiosity, hopelessness and gender have a significant influence towards Islamic financial literacy. Thus, this study suggests that it is important for the community, university administrators, government and financial advisor to increase the level of Islamic financial literacy by implementing various Islamic financial education programmes. Lastly, this study is considered as one of the studies that have contributed to the literature by developing understanding of Islamic financial literacy. More research related to Islamic financial literacy is suggested to be conducted for future research.